Identifying the effective factors on the transition to the third-generation university: A qualitative study - Mohammadreza Amiresmaili; Hossein Saberi; Farshid Barkhordari (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Iranian universities optimistically can be regarded as second-generation research-centered universities which train people who can only fill the predefined occupational gaps. These universities are doing very little to become third-generation universities. It seems that medical science universities have a huge capacity to create and expand entrepreneurship in health care because of their diverse activities in health services. The present study aimed to investigate the effective factors affecting the Iranian medical universities transition to third-generation universities. METHODS: The present study is a qualitative study which was carried out in Kerman University of Medical Sciences. The study population was the faculty members of Kerman University of Medical Sciences who had been selected by purposeful sampling method. For this purpose, 13 faculty members of Kerman University of Medical Sciences who were interested in the topic were interviewed. To collect data, a number of general questions were asked from the participants to clarify specific topics. The interviews lasted between 20 and 45 min. The descriptive phenomenology method was used for data analysis based on the Colaizzi's seven steps. RESULTS: In the present study, five main themes include; reforming the bureaucracy, paying attention to the empowerment of university personnel, improving the status of graduates, reviewing the status of education and research, and connecting with the industry and making a profit were identified. CONCLUSION: We can use strategies such as reduction of bureaucracy, privatization, reduction of management pyramid, culture building, creation of appropriate reward system, and taking a role model from successful people.